2020
DOI: 10.1080/00365521.2020.1713210
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term efficacy of adalimumab in ulcerative colitis: a real-life study

Abstract: Objective: Randomized controlled trials have shown the effectiveness of Adalimumab in ulcerative colitis. However, real-life data is scarce. We aimed to assess the effectiveness and predictive factors of effectiveness in a large Swedish cohort. Methods: Retrospective capture of data from local registries at five Swedish IBD centers. Clinical response and remission rates were assessed at three months after starting adalimumab treatment and patients were followed until colectomy or need for another biological. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Other studies have also certified that adalimumab can control most UC cases as soon as the 8th week of therapy and maintain this response up to the 52nd week (18,19). Angelison et al's study conducted on 118 UC patients with adalimumab for 3 months achieved clinical remission among 77% of participants, and the response rate of those with a history of treatment with infliximab was lower than naive patients (73% and 85%), which is in line with the results of the current study (20). Another study by Balint et al investigated adalimumab efficacy on 73 refractory UC cases (15).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other studies have also certified that adalimumab can control most UC cases as soon as the 8th week of therapy and maintain this response up to the 52nd week (18,19). Angelison et al's study conducted on 118 UC patients with adalimumab for 3 months achieved clinical remission among 77% of participants, and the response rate of those with a history of treatment with infliximab was lower than naive patients (73% and 85%), which is in line with the results of the current study (20). Another study by Balint et al investigated adalimumab efficacy on 73 refractory UC cases (15).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, in Balint et al's study, 5.4% of moderate to severe UC cases required colectomy during the first (31). Based on different studies, the most common side effects related to IBD treatment with adalimumab include infections (11 -34%), malignancies (1.9%), and demyelinating disorders (0.7%) (17,20,24,31). The report of no side effects in the current study proved that there is no new concern about the adalimumab safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world data supported the efficacy of adalimumab often showing improved performance [ 22 - 23 ]. This could be explained by varying reported outcomes and patients requiring dose-escalation being classed as treatment responders.…”
Section: Reviewmentioning
confidence: 99%
“…A retrospective cohort study based on data from the ENEIDA registry reported that failure to achieve response at 12 weeks was a clinical predictor of colectomy [ 8 ]. A randomized controlled trial reported that high C-reactive protein (CRP) levels, primary sclerosing cholangitis comorbidity, and female sex were predictors of failure [ 9 ]. Previous biologic exposure and disease activity at eight weeks after induction were also reported to be predictors of ADA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Predictive factors for primary and secondary failure have been reported [8][9][10][11]. A retrospective cohort study based on data from the ENEIDA registry reported that failure to achieve response at 12 weeks was a clinical predictor of colectomy [8].…”
Section: Introductionmentioning
confidence: 99%